2005
DOI: 10.1007/s10705-004-5084-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiency by maize as affected by a mucuna short fallow and P application in the coastal savanna of West Africa

Abstract: Maize is the primary food crop grown by farmers in the coastal savanna region of Togo and Benin on degraded (rhodic ferralsols), low in soil K-supplying capacity, and non-degraded (plinthic acrisols) soils. Agronomic trials were conducted during 1999-2002 in southern Togo on both soil types to investigate the impact of N and P fertilization and the introduction of a mucuna short fallow (MSF) on yield, indigenous N supply of the soil, N recovery fraction and internal efficiency of maize. In all plots, an annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
2
15
1
Order By: Relevance
“…We observed lower apparent N recovery compared to an average of 21-27% when N was added alone and 36-45% when N and P were added together in maize farm in coastal savanna of West Africa (Fofana et al, 2005). In addition, Fofana et al (2005) indicated that addition of N and P together significantly improved the apparent N uptake compared to adding N alone, which was not the case in this study. We broadcasted the fertilizer without manually mixing it with the soils.…”
Section: Effects Of Nutrient Enrichment On Anr and Nuecontrasting
confidence: 63%
“…We observed lower apparent N recovery compared to an average of 21-27% when N was added alone and 36-45% when N and P were added together in maize farm in coastal savanna of West Africa (Fofana et al, 2005). In addition, Fofana et al (2005) indicated that addition of N and P together significantly improved the apparent N uptake compared to adding N alone, which was not the case in this study. We broadcasted the fertilizer without manually mixing it with the soils.…”
Section: Effects Of Nutrient Enrichment On Anr and Nuecontrasting
confidence: 63%
“…Averaged over three seasons at sole 100 kg ha -1 N application, NCE was significantly higher on infields compared to outfields (0.52 vs. 0.38 kg kg -1 ). In a related experiment on degraded and non-degraded soils in Togo, Fofana et al (2005) also demonstrated that NCE was always superior on a non-degraded soil. Significant improvements in the NRE of applied N and overall NCE on the degraded soil was only realized when N and P were simultaneously applied.…”
Section: Resultsmentioning
confidence: 72%
“…Increases in the yield of cereal crops following the cultivation of legumes relative to those obtained with continuous cereal cropping have been frequently reported in the Guinea savannah (Muhr et al 1999b;Alvey et al 2001;Franke et al 2004;Fofana et al 2005). Often the amount of N and sometimes phosphorus (P) available to cereals improves in legume-cereal rotations.…”
Section: Introductionmentioning
confidence: 99%